2021
DOI: 10.3390/cells10102538
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Cardiac Tissue Engineering for the Management of Myocardium Infarction

Abstract: Myocardium Infarction (MI) is one of the foremost cardiovascular diseases (CVDs) causing death worldwide, and its case numbers are expected to continuously increase in the coming years. Pharmacological interventions have not been at the forefront in ameliorating MI-related morbidity and mortality. Stem cell-based tissue engineering approaches have been extensively explored for their regenerative potential in the infarcted myocardium. Recent studies on microfluidic devices employing stem cells under laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 220 publications
(256 reference statements)
0
14
0
2
Order By: Relevance
“…In the future, in order to further relieve patients' pain and reduce the risk and difficulty of surgery, spraying, injection, and 3D printing of cardiac patches would be the mainstream direction. [58] Although the use of minimally invasive method to produce cardiac patches has been reported before, like many current biomaterial cardiac patch normally requires open-chest surgery, our patch didn't avoid this operation, hampering its application for mild-to-moderate patients with heart failure after MI. [59] Thus, minimally invasive method should be further developed, not only relieving the patients' pain, but also easing the operation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the future, in order to further relieve patients' pain and reduce the risk and difficulty of surgery, spraying, injection, and 3D printing of cardiac patches would be the mainstream direction. [58] Although the use of minimally invasive method to produce cardiac patches has been reported before, like many current biomaterial cardiac patch normally requires open-chest surgery, our patch didn't avoid this operation, hampering its application for mild-to-moderate patients with heart failure after MI. [59] Thus, minimally invasive method should be further developed, not only relieving the patients' pain, but also easing the operation.…”
Section: Discussionmentioning
confidence: 92%
“…In the future, in order to further relieve patients’ pain and reduce the risk and difficulty of surgery, spraying, injection, and 3D printing of cardiac patches would be the mainstream direction. [ 58 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies are still in their early stages, and it could take decades to achieve 12 Stem Cells International clinical translational applications. In addition, engineering materials have provided some new ideas for the treatment of MI [34]. Patches were used to provide mechanical support to improve outcomes in the early days after MI, and subsequent studies reported the development of patches equipped with anti-inflammatory activity, but they could not compensate for the loss of cardiomyocytes [29].…”
Section: Discussionmentioning
confidence: 99%
“…Эритропоэтин не должен применяться в лечении больных ХСН даже при сниженном уровне гемоглобина [1,113] Стимуляция регенеративного потенциала сердечной мышцы В передовых научных центрах ведется накопление материала по четырем основным направлениям [118][119][120][121][122][123][124][125][126][127][128]:…”
Section: заключениеunclassified